Population density of plant-parasitic nematodes in rice fields associated with environmental variables in Malang, Indonesia - Hagus Tarno; Jaliaman Sipayung; Yogo Setiawan; Anton Meilus Putra; Jianguo Wang; Kunihiko Hata (Cogent Food & Agriculture)
Plant-parasitic nematodes (PPNs) are significant agricultural pests that cause substantial crop losses globally. This study investigated the abundance and distribution of PPNs concerning elevation in rice fields in Malang District, East Java, Indonesia. Nematodes were sampled across elevation gradients between 0 to over 1000 meters above sea level (masl). Pratylenchus, Aphelenchoides, and Longidorus, were found in the soil and rice roots in Malang District. Pratylenchus dominated the relative abundance of PPNs in the soil at 0–400 masl, whereas Longidorus dominated at 600 to > 1000 masl. In rice root samples, Pratylenchus sp. also dominated at 0–400 masl and Longidorus was dominated at 800-100 masl. The population density of Pratylenchus negatively correlated to elevation, pH, soil organic matter, and carbon organic. However, soil temperature positively correlated with the population density of Pratylenchus. Elevation and pH showed a negative influence on the population density of Aphelenchoides, whereas soil temperature showed a positive influence on the population density of Aphelenchoides. Soil temperature negatively correlated to the population density of Longidorus, whereas elevation and soil humidity positively influenced the population density of Longidorus. However, the population density of Longidorus increased with higher elevation and soil humidity. Understanding the specific relationships between PPN populations and environmental factors is essential for developing effective pest management strategies. Targeted approaches that consider these ecological dynamics can help mitigate crop damage and enhance rice production in varying environmental conditions, especially in the Java region.